2-Guanidinoethanesulfonyl sesquiterpenes from the marine sponge Agelas nakamurai. (3rd August 2022) - Fu, Chung-Wei; Lin, You-Cheng; Chiou, Shu-Fen; Huang, Tzu-Yin; Yang, Yen-Ju; Wu, Shih-Hsiung; Chen, Shu-Li; Lin, Chi-Chien; Wang, Hui-Chun; Yu, Meng-Chen; Sheu, Jyh-Horng
Graphical abstract: Abstract: A new 2-guanidinoethanesulfonyl sesquiterpene, cyclohexylagelasidine A (1 ), and a known compound (–)-agelasidine A (2 ), were isolated in the present chemical investigation of a marine sponge Agelas nakamurai . Cyclohexylagelasidine A (1 ) is the first 2-guanidinoethanesulfonyl sesquiterpene with a carbocyclic ring in nature. Moreover, the major metabolite 2 showed cytotoxic, antibacterial, and anti-inflammatory activities.